UNDERSTANDING THE CHARACTERISTICS OF A SPEECH BASED ON GENDER-BASED CONVERSATIONS - Adi, Pidekso (Jurusan Sastra Indonesia, 2023)
conversation is the embodiment of human expression by procedures, methods, and resources associated with the context. The context becomes the deciding factor that gives the perception between the speaker and the hearer so that the conversation interactive. Interactivity conversation that occurs because of the efforts of the speakers to interpret utterances addressees so as to make it a meaningful conversation. Conditions for mutual interpret perspective that is referred to as reciprocity of perspective. The existence of reciprocity of perspective, the conversation will be dynamic. Thus, the existence of reciprocity of perspective on the identity of the speaker and hearer are caused by the difference between the sexes will affect the process of speech. If the speaker's gender to male perspective to the addressees subordinate female then reciprocity will be different perspectives with speakers of the male sex who have different perspectives of the speakers superordinatif female.